Studies in Acoustical properties of Glycyl-Glycyl-Glycine Peptide in 20% Dioxane-Water Mixture at Different Temperatures - KIRNAPURE, K.T.; KHOBRAGADE, B.G. (Asian Journal of Chemistry, 2010)
Ultrasonic velocities and densities of glycyl-glycyl-glycine (GGG) peptide in 20% dioxane-water mixture have been evaluated at different temperatures, 298, 303, 308, 313 and 318 K, by using single crystal interferometer at a frequency of 20 MHz. The ultrasonic velocity, density and concentration were used to calculate (i) partial molal volume φv, (ii) adiabatic compressibility βg, (iii) Apparent molal compressibility φk(s), (iv) intermolecular freelength Lf, (v) specific acoustic impedance (Z), and (vi) relative association (RA) through the light on the solute-solvent and solute-solute interaction. It is observed that φv0 values increase gradually with increase in temparature, but there is no regular order of φk(s)0 with respect to temperature. The value of φk(s)0 decreases up to 303 K and further that the values of φk(s)0 increase gradually. The data of φv0 at different temperatures are used to determine that thermodynamic parameters such as free energy ΔG, enthalpy ΔH and entropy ΔS for glycyl-glycyl-glycine in 20% dioxane-water mixture. The values of ΔG, ΔH, ΔS are found to be 3928.4 calories, 8311.22 calories and 278.88 calories respectively. The value of ΔG < 0 and the value of ΔS > 0 indicate the spontaneous process (i.e., forward direction process.)